Bulletin 65 Oil and Gas Wells Through Workable Coal Beds - George S. Rice; O. P. Hood (The National Institute for Occupational Safety and Health (NIOSH), 1913)
The need of protecting mines from the danger of inflow of natural gas from neighboring wells has become more apparent each year since it was found that oil and gas underlie the productive coal measures of Pennsylvania, West Virginia, Ohio, Indiana, Illinois, Kansas, Oklahoma, Colorado, and Wyoming, and, to some extent, the coal measures of other States. The proximity of the known gas and oil areas in the United States to the coal fields and the manner in which the fields overlap in certain States are shown in the map comprising the frontispiece (Pl. I). As the result of many requests received from various sources a conference to consider the protective measures necessary to insure the safety of mining operations in gas and oil fields was called by the Director of the Bureau of Mines to assemble in Pittsburgh, Pa., Feb- ruary 7 and 8, 1913. To this conference were invited a considerable number of gas-well, oil-well, and coal-mine operators within conven- ient distance from Pittsburgh, as well as State geologists and State mine inspectors from a distance. Gas and oil wells are also found near other kinds of mines, such as shale and limestone mines in western Pennsylvania, but these cases are so few that for this and other reasons it was deemed best to con- fine the present inquiry to the consideration of the questions involved in connection with coal mines. It was also not thought advisable to consider the protection of mines from other kinds of bore holes than those for gas and oil, such as coal-prospecting holes, drilled either with churn or diamond drills, or salt wells and artesian wells, because little trouble has been ex- perienced in mining operations from these classes of wells. There- fore the following papers and discussions concern almost entirely the following relations between coal mines and gas and oil wells: (1) Protection of coal mines froin gas and oil wells penetrating -through: (a) Open workings; (b) inaccessible spaces or goaves; (c) pillars, or coal which may be left as pillars. (2) The manner of drilling gas and oil wells passing through workable coal beds so as to provide protection for future mining. The preliminary inquiries of the engineers of the bureau had dis- closed that there was no uniformity in the methods of protecting mines against the leakage of gas from wells, that thousands of wells in coal fields are abandoned yearly without adequate plugging, and without surveys or records being kept to show the location of the holes, from which the casings are generally pulled. According to the State geologist of Pennsylvania, as many as 3,000 wells are being drilled annually in Pennsylvania, 2,000 of these holes being aban- doned within a single year. It is such unplugged, uncharted wells that are the greatest menace in mining. The quantity of gas that the wells produce, although not sufficient to be commercially avail-